2004
DOI: 10.1203/01.pdr.0000112032.47575.d1
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of the Ketogenic Diet on Cognitive Function in Rats

Abstract: The ketogenic diet (KD) is a high-fat, low-carbohydrate, and low-protein diet that is widely used to treat epilepsy in children. Although the KD has been shown to be efficacious in the treatment of childhood epilepsy, the long-term effects of the KD on brain development are not clear. The objective of this study was to examine the long-term effects of the KD on visual-spatial memory, activity level, and emotionality in immature rats after status epilepticus (SE). Weanling rats were subjected to lithium/ piloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 67 publications
3
86
2
1
Order By: Relevance
“…Clinically, the KD is associated with significantly attenuated growth compared to humans consuming a non-KD (Vining et al, 2002;Liu et al, 2003;Papandreou et al, 2006). This has also been shown in rats fed a KD (Zhao et al, 2004;Nylen et al, 2005;Nylen et al, 2006). This held true in the KD fed mutants as they showed significant stunting of growth when compared to CD fed wildtype mice.…”
Section: Ataxia and Weightsmentioning
confidence: 68%
See 1 more Smart Citation
“…Clinically, the KD is associated with significantly attenuated growth compared to humans consuming a non-KD (Vining et al, 2002;Liu et al, 2003;Papandreou et al, 2006). This has also been shown in rats fed a KD (Zhao et al, 2004;Nylen et al, 2005;Nylen et al, 2006). This held true in the KD fed mutants as they showed significant stunting of growth when compared to CD fed wildtype mice.…”
Section: Ataxia and Weightsmentioning
confidence: 68%
“…We did not measure weight gain in KD fed Aldh5a1 +/+ mice. There are several studies, both clinical and experimental, that report KD fed subjects being lighter than normal diet fed subjects (Rho et al, 1999;Bough & Eagles, 2001;Vining et al, 2002;Zhao et al, 2004;Nylen et al, 2005). Despite having significantly stunted growth, rodents fed a KD do not experience anywhere near the stunting seen in SSADH mutants fed either a KD or a CD.…”
Section: Ataxia and Weightsmentioning
confidence: 99%
“…RNA in situ hybridization was performed as described previously (31). Timm staining was performed by using a modification of a previously published protocol (30,32). Briefly, a 1-month-old rat (125 g body weight) was anesthetized by 3.5 ml of 1.25% Avertin solution i.p.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to this clinical finding, an experimental study has also reported cognitive and behavioral adverse consequences. Zhao et al (2004) tested weanling rats maintained on a ketogenic diet for 30 days in the Morris water maze, open field test, brain weights, time to seizure onset, and hippocampal cell loss. No ketogenic effects were found in the activity, emotionality, or pathology, but there was significant reduction in seizure activity.…”
Section: Adverse Effects Of Ketonesmentioning
confidence: 99%